Multilayer strategy and mechanical grinding for smoothing CVD diamond coated defective substrate. (5th August 2016) - Chen, Naichao; Ai, Jun; Chen, Yingchao; He, Ping; Ren, Jianxin; Ji, Dongmei
Abstract: Surface quality of substrate easily affects the surface morphology of chemical vapor deposition (CVD) diamond coating. However, the fragile and hard substrate often has many defects in the surface. In this work, a novel method is proposed by the conventional CVD technique combining multilayer strategy and mechanical grinding, with which the smooth CVD diamond coating can be produced on the defective substrate. The microcrystalline diamond (MCD) coating is first deposited on the defective substrate to reinforce the adhesive strength of coating. Mechanical grinding are subsequently adopted by directly polishing the surface to quickly smooth the MCD coating. The second-layer MCD coating continues to be deposited on the polished coating. The surface becomes relatively smooth. For further smoothing the coating, the second-layer MCD coating is also polished, and the nanocrystalline diamond (NCD) coating is deposited as the top layer. The results show the MCD/MCD/NCD coating has a smooth surface with the Ra of 134 nm. Turning test shows that the as-deposited diamond coating possesses high adhesive strength and strong wear resistance. The results prove that our method is adequate for the defective substrate to fabricate a smooth coating by repeating surface polishing and diamond deposition. Graphical abstract: Highlights: A novel method is proposed to obtain the smooth diamond coated defective surface. Mechanical grinding is adopted to quickly flat the diamond surface. The polishing-depositing procedure progressively decreases the surface roughness. The deposited multilayer diamond coating shows a superior mechanical properties.